Computer-Based Exercises in Anemia Diagnosis (PlanAlyzer) - Beck, J. R.; O´Donnell, J. F.; Hirai, F.; Simmons, J. J.; Healy, J. C.; Lyon, H. C. (Methods of Information in Medicine, 1989)
PlanAlyzer is a microcomputer-based, event-driven system for instructional research in medical education. Aimed at the second year medical student, PlanAlyzer elicits and critiques a student´s approach to the diagnosis of a common medical disorder. In this paper we discuss the concept, development, implementation and formative evaluation of the PlanAlyzer system for the evaluation of anemia.
Keywords: Computer-assisted Diagnosis; Artificial Intelligence; Computer-assisted Instruction; Hematology